ISLAMIC MYSTICISM AND SPIRITUALITY: ANALYZING THE ROLE OF SUFISM IN MODERN MUSLIM SOCIETY - Makhrus Ali; Nina Anis; Nurul Huda; Mujiburrohman Mujiburrohman (Yayasan Adra Karima Hubbi, 2026)
Islamic mysticism and spirituality have long constituted a central dimension of Muslim religious life, with Sufism serving as a primary vehicle for cultivating inner piety, ethical refinement, and experiential knowledge of the Divine. In contemporary Muslim societies shaped by modernization, globalization, and shifting religious expressions, the relevance and function of Sufism continue to be debated. This study aims to analyze the role of Sufism in modern Muslim society by examining its spiritual, ethical, and social significance within contemporary contexts. The research employed a qualitative interpretive design, drawing on semi-structured interviews, textual analysis of contemporary Sufi discourses, and observational data from selected Sufi communities. Data were analyzed thematically to identify recurring patterns related to spirituality, social engagement, and adaptation to modern life. The findings reveal that Sufism remains a meaningful and adaptive form of Islamic spirituality, contributing to personal spiritual fulfillment, ethical orientation, and social cohesion. Engagement with Sufi practices was associated with inner discipline, emotional balance, and a heightened sense of moral responsibility. The study concludes that Sufism functions as a dynamic spiritual resource rather than a residual tradition, offering frameworks for meaning-making and ethical engagement in modern Muslim society.